Cultural narratives of basketball participation and psychological resilience: a mixed-methods study among university students in China, the USA, and Europe - Li, Jie; Wang, Jianping; Liu, Yueting; Li, Lei (Frontiers in Psychology, 2025)
Against the backdrop of increasing concern over mental health in higher education, psychological resilience has become a central topic in educational psychology, serving as a key indicator of students' capacity to cope with stress and recover from adversity. This study focuses on campus basketball culture and investigates how it influences the development of psychological resilience among university students, with particular attention to cross-cultural variations in this process. Drawing on a mixed-methods design, the research integrates data from 2,700 questionnaire responses and 18 semi-structured interviews across three cultural contexts: China, the United States, and Europe. The results demonstrate that social dimensions of campus basketball culture—especially perceived peer support—play a significant positive role in fostering psychological resilience. However, the strength and structure of this relationship differ across cultural groups. Chinese students tend to rely more on a “team support–emotional security” pathway, American students emphasize “individual challenge–self-motivation,” while European students exhibit a hybrid mechanism characterized by “interactive balance and cultural adaptation.” The interview findings further reveal diverse cultural patterns in value orientation, identity formation, and emotional expression within the resilience-building process. This study contributes to the theoretical integration of sports psychology and cross-cultural psychology, while offering practical insights for implementing culturally responsive sports-based mental health interventions in universities.